2020
DOI: 10.1029/2019jc015500
|View full text |Cite
|
Sign up to set email alerts
|

On the Differences Between the South Pacific Meridional and Quadrupole Modes

Abstract: The South Pacific quadrupole (SPQ) and South Pacific meridional mode (SPMM) are the dominant modes of South Pacific sea surface temperature (SST) variability. Both SST modes have been found to affect the occurrence of El Niño-Southern Oscillation (ENSO) events. In this study, the authors examine the differences between the SPQ and SPMM in terms of their spatial structure, temporal variations, and impacts on ENSO using observational and Coupled Model Intercomparison Project Phase 5 (CMIP5) model data. As a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The heat-value-highlighted JFM(0) SSTA over the south Pacific can be traced back to the South Pacific quadrupole (SPQ) mode, which is characterized by quadrupole-like SSTAs over the south Pacific. Previous studies (Ding et al, 2015(Ding et al, , 2019(Ding et al, , 2020Qin et al, 2017) have suggested SPQ serves as a precursor of ENSO. This finding here is probably among the first to report SPQ plays a role in ENSO prediction in DL models.…”
Section: Physical Interpretation Of Enso Forecasts At a Leadmentioning
confidence: 94%
“…The heat-value-highlighted JFM(0) SSTA over the south Pacific can be traced back to the South Pacific quadrupole (SPQ) mode, which is characterized by quadrupole-like SSTAs over the south Pacific. Previous studies (Ding et al, 2015(Ding et al, , 2019(Ding et al, , 2020Qin et al, 2017) have suggested SPQ serves as a precursor of ENSO. This finding here is probably among the first to report SPQ plays a role in ENSO prediction in DL models.…”
Section: Physical Interpretation Of Enso Forecasts At a Leadmentioning
confidence: 94%